Migration in the Southern Balkans: From Ottoman Territory to Globalized Nation States - Vermeulen, Hans (Springer, 2015)
This volume collects ten essays that look at intra-regional migration in the Southern Balkans from the late Ottoman period to the present. It examines forced as well as voluntary migrations and places these movements within their historical context, including ethnic cleansing, population exchanges, and demographic engineering in the service of nation-building as well as more recent labor migration due to globalization.